Dukungan Sosial, Kesulitan Regulasi Emosi, dan Resiliensi Siswa (Indonesian Journal of Guidance and Counseling: Theory and Application, 2021)
A lot of stressful situations and various problems of students, make resilient attitude very important to be explored further. This reserch aims to identify the relationship between social support and emotional regulation difficulties with resilience of students. The sample involved 304 students (44% male and 56% female) selected using stratified random sampling. Data were collected using the instrument of Multidimentional Scale of Perceived Social Support (MSPSS) adapted from Canty-Mitchell dan Zimet (2000), Difficulties in Emotion Regulation Scale (DERS) adapted from Gratz dan Roemer (2004), dan Resilience Scale (RS) adapted from Wagnild dan Young (1987). The findings of this study indicate that the source of support comes from friends and two types of difficulties of emotional regulation correlate with resilience. Therefore, it is suggested for the counseling teachers teachers to be able to give a valuable service that can increase student resilience.